A Survey on Tetanus Toxoid (TT) Vaccination Status of Women of Reproductive Age (15 - 49 years) in a Rural Community of Satkhira - Ferdaus, Farhana; Hussain, Rubaiyat Farzana; Biswas, Sailendra Nath; Haque, AQM Ataul; Sultana, Nahida (KYAMC Journal, 2019)
Background: Tetanus is a preventable disease. No age is immune unless protected by previous vaccination. Infection generally occurs through wound infection and unhygienic condition of child birth. Objective: To find out the TT vaccination status of women of reproductive age group. Materials and Method: This cross-sectional type of descriptive study was carried out during January, 2017 to May 2017. Data were collected from 219 respondents selected by purposive type of sampling through face to face interview using a pretested mixed type of questionnaire. Results: Among total respondents, majority 53 (24.20%) were belonged to 20-25 years of age group. Two hundred and fourteen (97.71%) of total respondents had knowledge about TT vaccination. In present study, 184 (84.02%) had coverage and among them 93 (42.47%) of respondents had completed their vaccination (5 doses). One hundred and seventy (92.39%) of respondents received vaccination from government organization. Current study also reflects gradual increase in health consciousness among young women as 44 (28.38%) of respondents completed vaccination before their first pregnancy. Conclusion: Acceptance of TT vaccination has been increased up to a satisfactory level. Another large scale study is recommended to find out TT coverage among all women of reproductive age group (15-49 years) of Bangladesh. KYAMC Journal Vol. 10, No.-2, July 2019, Page 73-76